2012
DOI: 10.1002/tal.1068
|View full text |Cite
|
Sign up to set email alerts
|

Proposed robust tuned mass damper for response mitigation in buildings exposed to multidirectional wind

Abstract: SUMMARY The most common device for control of tall buildings under wind loads is the tuned mass damper (TMD). However, during their lifetimes, high‐rise and slender buildings may experience natural frequency changes under wind speed, ambient temperatures and relative humidity variations, among other factors, which make the TMD design challenging. In this paper, a proposed approach for the design of robust TMDs is presented and investigated. The approach accounts for structural uncertainties, optimization objec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 36 publications
0
43
0
Order By: Relevance
“…LQR control algorithm: In order to evaluate effectiveness of the proposed IBFC, semi‐active system with the LQR algorithm, which has been developed by Kurata et al, was used to compare the results. LQR is widely used in optimum control techniques in structural control problems that finds an active control parameters to minimize the cost function given by the form: J=120.25em0(),ztT[],Q{},z(),t+utT[],R{},u(),t0.25emitalicdt. …”
Section: Implementation Of the Proposed Control System In Buildingsmentioning
confidence: 99%
“…LQR control algorithm: In order to evaluate effectiveness of the proposed IBFC, semi‐active system with the LQR algorithm, which has been developed by Kurata et al, was used to compare the results. LQR is widely used in optimum control techniques in structural control problems that finds an active control parameters to minimize the cost function given by the form: J=120.25em0(),ztT[],Q{},z(),t+utT[],R{},u(),t0.25emitalicdt. …”
Section: Implementation Of the Proposed Control System In Buildingsmentioning
confidence: 99%
“…In fact, providing researchers with data on wind turbine design and performance would allow wind turbines to be optimized . Future research will focus on the control of the response of the wind turbine using potential active and semi active techniques, similar to those used for the control of buildings under wind and earthquake loads (; Rezaee and Aly ).…”
Section: Effects Of Base Dynamics On Foundation Loadsmentioning
confidence: 99%
“…passive, active and semi-active, is not only for structures subjected to earthquake excitations. There are many studies that have shown that these strategies are effective in the response reduction of buildings under strong wind loads (Huang and Chou, 1995;Wu and Pan, 2002;Aly et al, 2011;Aly, 2014).…”
Section: Introductionmentioning
confidence: 99%